ANALISIS KEBERADAAN BADAN USAHA MILIK DESA (BUMDES) SEBAGAI ACUAN PENINGKATAN EKONOMI DESA (Studi Kasus di Desa Koto Beringin Kecamatan Hamparan Rawang Kota Sungai Penuh): H. EDWIN BUSTAMI, SE., MM - Edwin Bustami (JURNAL ADMINISTRASI NUSANTARA, 2019)
This study aims to find out how the existence of village-owned enterprises as a reference for improving village economy in the Koto Beringin Village Hamparan Rawang District Sungai Penuh City. This type of research is qualitative research. Data collection techniques in this study used the method of observation and interviews conducted on 7 (seven) informants who were the village government, village-owned enterprises (BUMDes) administrators and the village community Koto Beringin sub-district of Hamparan Rawang, Sungai Penuh City. The finding of research show that the existence of a village-owned enterprises (BUMDes) in the village of Koto Beringin sub district Hamparan Rawang in Sungai Penuh City can be a forum for reference to improving the village economy even though it has not been seen significantly and not all people anjoy it. Rather than that there are several aspects that show how the existence of village-owned enterprises (BUMDes) can be a reference for improving the village economy, which is seen from : Village Income per Capita, Income Inequality, Changes in economic structure, and growth in employment opportunities. The existence of village-owned enterprises (BUMDes) in rural economic development efforts will be better if the management of village-owned enterprises (BUMDes) is increased again, then there is also a need for renewal or innovation in the village-owned enterprises (BUMDes) area on (WTC) so that visitors cn increase so that village and communities can beneffit from it.